(Grund-)Steuerreform: die Diskussion der länderoffenen Arbeitsgruppe der Finanzminister - Dirk Löhr (Wirtschaftsdienst, 2012)
Die Einheitswerte für Immobilien, auf die sich die Grundsteuer bezieht, wurden vom Bundesfinanzhof als verzerrend angesehen. Eine Arbeitsgruppe der Finanzminister beschäftigt sich schon seit Anfang 2010 mit diesem Problem. Dabei haben sich drei Modelle herauskristallisiert, die den Boden- und den Grundstückswert unterschiedlich gewichten. Der Autor plädiert hier für eine am Bodenwert orientierte Bemessungsgrundlage. – – Currently, property tax reform is again on the political agenda in Germany. A working group of the ministries of finance of the German states has shortlisted three proposals, whose tax bases comprise land as well as the existing building. Apparently, the previous discussion on property tax reform was widely ignored. In order to meet the requirements of the law, a compound tax base requires expensive assessments. Moreover, it discourages the efficient use of sites and encourages owners to pass on the tax to tenants. It causes a decoupling of the benefits and costs of land-use. A tax based on site value might avoid all these aberrations. It is strange that this alternative is not taken into consideration more carefully.
Keywords: H21; H22; H23; H71; R14; R51; 330; Grundsteuer; Steuerreform; Steuerbemessung; Grundbesitz; Deutschland